2018
DOI: 10.3389/fpls.2018.00388
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Biometric Traits, Yield and Nutritional and Antioxidant Properties of Seeds of Three Soybean Cultivars Through the Application of Biostimulant Containing Seaweed and Amino Acids

Abstract: In recent years, attempts have been made to use preparations that allow obtaining high and good quality yields, while reducing the application of pesticides and mineral fertilizers. These include biostimulants that are safe for the natural environment and contribute to the improvement of yield size and quality, especially after the occurrence of stressors. Their use is advisable in the case of crops sensitive to such biotic stress factors like low temperatures or drought. One of these is soybean which is a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 78 publications
8
41
0
8
Order By: Relevance
“…Similar results have been reported for total phenols and flavonoids contents of soybean seeds after the application of two synthetic biostimulants (Atonik and Tytanit), where, despite the different response being observed during a 3 year study, the application of biostimulants in a high single doses gave consistently the best results . Polyphenols and flavonoids content of seeds from three soybean cultivars was also affected by natural biostimulants application such as Fylloton (a complex of amino acids and seaweed extracts) in a dose and cultivar‐dependent manner . The beneficial effect of biostimulants on phenolic compounds composition and content of snap bean pods was also reported in the case of garlic clove extracts and associated with its high content in phytohormones such as jasmonic and salicylic acids .…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Similar results have been reported for total phenols and flavonoids contents of soybean seeds after the application of two synthetic biostimulants (Atonik and Tytanit), where, despite the different response being observed during a 3 year study, the application of biostimulants in a high single doses gave consistently the best results . Polyphenols and flavonoids content of seeds from three soybean cultivars was also affected by natural biostimulants application such as Fylloton (a complex of amino acids and seaweed extracts) in a dose and cultivar‐dependent manner . The beneficial effect of biostimulants on phenolic compounds composition and content of snap bean pods was also reported in the case of garlic clove extracts and associated with its high content in phytohormones such as jasmonic and salicylic acids .…”
Section: Resultssupporting
confidence: 64%
“…9 Polyphenols and flavonoids content of seeds from three soybean cultivars was also affected by natural biostimulants application such as Fylloton (a complex of amino acids and seaweed extracts) in a dose and cultivar-dependent manner. 35 The beneficial effect of biostimulants on phenolic compounds composition and content of snap bean pods was also reported in the case of garlic clove extracts and associated with its high content in phytohormones such as jasmonic and salicylic acids. 36 In our study, the prolonged effect of water stress (pods of the second harvest and seeds) resulted in a decrease of phenolic compounds content, whereas the G treatment showed the highest increase compared with the control, regardless of the irrigation treatment.…”
Section: Comparative Analysis Of Phenolic Content In Each Seed and Pomentioning
confidence: 82%
“…Numerous studies conducted on arable crops confirmed the beneficial effect of seaweed extracts on increasing yield components [11,12,47,[64][65][66]. Previous research on other bean and soybean varieties confirmed the stimulating effect of the Ecklonia maxima or Ascophyllum nodosum extracts on the number of pods and seeds, and the weight of beans [39][40][41]67]. The lack of effect of Kelpak on the one-thousand-seed weight of bean was also confirmed by previous studies on common bean [66].…”
Section: Discussionmentioning
confidence: 54%
“…In our research, combining the Fylloton biostimulant, which induces the extract's effect, with Ascophyllum nodosum and amino acids increased the yield components, particularly the number of seeds after its double application. Moreover, previous studies, conducted on three soybean varieties, confirmed that this preparation has a positive effect on the number of pods and seeds, as well as seed yield [40]. The application of Fylloton in the cultivation of winter oilseed rape positively influenced the increase in the number of pods, the yield of seeds, and the weight of one thousand seeds, especially after applying the biostimulant together with the Perfektmikro micronutrient fertilizer containing EDTA-chelated (ethylenediaminetetraacetic acid-chelated) manganese, copper, iron, and zinc, as well as molybdenum, boron, and nitrogen [121].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation